Development of Student Worksheets with Contextual Teaching and Learning Approach for Learning Ecosystem - Sitorus, Ravita; Ulfa, Syarifah Widya (Jurnal Pendidikan MIPA, 2023)
Biology learning at SMAS Taman Siswa Sukadamai has not used worksheets as teaching materials, teachers only use textbooks in the learning process so that the teacher-centered biology learning process becomes uninteresting and monotonous. This study aims to produce ctl-based worksheets on ecosystem material. The model used in this study is the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. This research data collection technique through interviews, observation, questionnaires and tests. The research results based on the assessment of material experts obtained a score of 88% and media experts by 92% with the category very suitable for use in learning. The teacher and student assessment responses during the try-out obtained a score of 90% for teachers and 83.37% for students in the very practical category for use in learning. The results of applying the CTL-based LKPD on ecosystem material to student learning outcomes obtained quite effective results with an n-gain value of 0.67 in the quite effective category. It can be interpreted that CTL-based worksheets on ecosystem material are very feasible and can be used in the learning process.Keywords: student worksheet, Contextual Teaching and Learning, Biology learning.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp191-202